Bulk‐filled posterior resin restorations based on stress‐decreasing resin technology: a randomized, controlled 6‐year evaluation. (19th May 2017) - van Dijken, Jan W. V.; Pallesen, Ulla
Abstract : This randomized study evaluated a flowable resin composite bulk‐fill technique in posterior restorations and compared it intraindividually with a conventional 2‐mm resin composite layering technique over a 6‐yr follow‐up period. Thirty‐eight pairs of Class II restorations and 15 pairs of Class I restorations were placed in 38 adults. In all cavities a single‐step self‐etch adhesive (Xeno V) was applied. In the first cavity of each pair, the flowable resin composite (SDR) was placed, in bulk increments of up to 4 mm. The occlusal part was completed with a layer of nanohybrid resin composite (Ceram X mono). In the second cavity of each pair, the hybrid resin composite was placed in 2‐mm increments. The restorations were evaluated using slightly modified US Public Health Service (USPHS) criteria at baseline and then annually for a time period of 6 yr. After 6 yr, 72 Class II restorations and 26 Class I restorations could be evaluated. Six failed Class II molar restorations, three in each group, were observed, resulting in a success rate of 93.9% for all restorations and an annual failure rate (AFR) of 1.0% for both groups. The AFR for Class II and Class I restorations in both groups was 1.4% and 0%, respectively. The main reason for failure was resin composite fracture.